Recessive Dystrophic Bullous Epidermolysis with Squamous Cell Carcinoma: A Rare Case Report - Sissy Sissy; Mahfudz Shidiq; Clara Virginia Allun; Daniel Ahmad Romero (Perkumpulan Kedokteran Militer, 2024)
Epidermolysis bullosa (EB) is a genetic disorder in which the skin layer and other epithelia attached to the underlying connective tissue are disrupted with a tendency to form blisters and vesicles after mild trauma or friction. Other organs, like as the esophagus, can be damaged by some forms of EB, and subsequent problems might require several procedures. While there has been substantial progress in illness classification, specifically identifying the genes and proteins involved, there have been limited advancements in disease therapy. The care of an EB patient focuses on suppressing symptoms, protection of the skin, and minimizing complications. This case report presents the unique case of a 13-year-old girl diagnosed with recessive dystrophic epidermolysis bullosa complicated by squamous cell carcinoma. Multiple erosional efflorescences appear geographically defined boundaries covered with brownish yellow crusts, dystrophic scars, milia. Contractures of both fingers and toes (pseudosyndactyly) were present. The diagnosis was established through a comprehensive evaluation including history, physical examination, and relevant tests. The patient's parents did not have any of these problems and were not linked. There is no family history of the patient suffering from comparable problems. Therapy is therefore focused on the prevention of lesions and complications. The complexity of the therapeutic strategy depends on the severity of the patient's lesions. Optimal management of this disease can only be done through a multidisciplinary team of different disciplines. The management given is Sodium Fusidate cream every 12 hours applied to open erosions, open compresses NaCl 0.9% every 8 hours for 15-20 minutes, on crusts, levertrans on erosion areas. The prognosis for individuals with this condition remains uncertain, highlighting the challenges in addressing the complex nature of this disease.